2015
DOI: 10.3923/biotech.2015.225.232
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Expression and Characterization of Multi Cassettes Encoding Indonesian Small Hepatitis B Surface Antigen (s-HBsAg) in Methylotropic Yeast Pichia pastoris

Abstract: A B S T R A C T Hepatitis B is the most common liver infection worldwide. The recombinant VirusLike Particles (VLP) of small Hepatitis B surface antigen (s-HBsAg) vaccine provides excellent protection against Hepatitis B Virus (HBV). In this study, we have generated a construct of Pichia pastoris recombinant which comprises multi expression cassettes encoding s-HBsAg which belongs to HBV B3 genotype predominantly found in Indonesia. An expression cassette containing a synthetic codon optimized open reading fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This stage aims to induce P. pastoris to produce sHBsAg protein using 2% methanol. The concentration has been showed by Giri-Rachman et al (2015) to have positive effect on growth and sHBsAg protein expression level. Besides, Santoso et al (2012) showed that 2.5% methanol can increase human erythropoietin gene expression in P. pastoris.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This stage aims to induce P. pastoris to produce sHBsAg protein using 2% methanol. The concentration has been showed by Giri-Rachman et al (2015) to have positive effect on growth and sHBsAg protein expression level. Besides, Santoso et al (2012) showed that 2.5% methanol can increase human erythropoietin gene expression in P. pastoris.…”
Section: Discussionmentioning
confidence: 99%
“…P. pastoris GS115 transformant culture, pAO815 plasmid harbouring single copy and four copies of sHBsAg expression cassette (pAO-HBs1 and pAO-HBs4) was obtained from previous study (Giri-Rachman et al 2015). Yeast DNA purification kit were purchased from Epicentre.…”
Section: Strains Plasmids and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations